Spectroscopic and Statistical Methods Used to Compare the Elemental Composition of Historical Samples - ORLIĆ , Mandi; BADOVINAC, İvana; ORLIĆ , Nada (International Journal of Computational and Experimental Science and Engineering, 2015)
For different purposes in investigation of cultural heritage samples, including ancient coins, it is necessary to use non-destructive and/or almost non-invasive spectroscopic techniques in combination with appropriate statistical methods. In this paper, we want to show some similarities and certain differences in the elemental composition of two bronze coins, produced for use in the same geographical area, but at different historical moments. We choose the experimental method of laser ablation or laser induced breakdown spectroscopy (LIBS) as well as two emission spectroscopy of x-rays, excited using radioactive source, or x-ray tube. Finally, in qualitative and quantitative interpretation of the multitude of data obtained by LIBS experiment, we used two methods of multivariate analysis, as follow: Principal component analysis (PCA) and Partial least squares (PLS) methods.